(untitled) (Bangladesh Journal of Medical Science, 2026)
Background Dental practice is recurrently implicated in occupational health discourse as a profession uniquely disposed to psychosocial strain by virtue of its technical precision imperatives, its intimate, anxiety-laden patient encounters, its economic self-reliance architecture, and its temporally compressed decision environment. Karasek’s Demand-Control-Support model offers an analytically tractable framework for decomposing this strain into constituent organizational dimensions. Objective To characterize occupational stress among Moroccan dental practitioners, delineate the distribution of Karasek job strain quadrants, and identify sociodemographic and professional correlates of the stress ratio. Methods An observational cross-sectional design was implemented among 223 Moroccan dental practitioners. The French-language version of the Job Content Questionnaire (JCQ) was administered, capturing psychological demands, decision latitude, skill discretion, decision authority, supervisor support, and coworker support. Internal consistency was evaluated via Cronbach’s alpha. Inferential analyses employed chi-square tests, Mann- Whitney U, Kruskal-Wallis tests, and Spearman rank correlations. Results The sample was predominantly female (59.2%), with a mean age of 36.6 ± 10.2 years and mean professional experience of 11.1 ± 9.0 years. The mean psychological demands score was 2.72 ± 0.39; mean decision latitude was 2.92 ± 0.52; and mean social support was 2.65 ± 0.58. The mean job stress ratio was 0.97 ± 0.24. Among classifiable participants, 31.7% occupied the active quadrant, 24.4% the high-strain quadrant, 23.1% the passive quadrant, and 19.0% the low-strain quadrant. Practice sector was significantly associated with the stress ratio (Kruskal-Wallis H = 6.58; p = 0.037), with the semi-public sector exhibiting the highest tension levels. Both age (ρ = -0.146; p = 0.033) and professional experience (ρ = -0.173; p = 0.011) were negatively correlated with the stress ratio. Conclusion Occupational stress constitutes a substantive and heterogeneously distributed burden among Moroccan dentists, with nearly one in four practitioners operating under high-strain conditions. Sector-specific organizational pressures and early-career vulnerability emerge as prioritized intervention targets Bangladesh Journal of Medical Science Vol. 25 No. 03 July’26 Page: 974-982